Risk of clinically significant prostate cancer undercategorized by multiparametric magnetic resonance imaging. - Zhu, Wangshu; Long, Haining; Yu, Weibin; Xiong, Yijia; Fu, Caixia; Zhao, Jungong; Liu, Xiaohong (Abdominal Radiology, 2025)
Background: To investigative potential clinicopathological characteristics and imaging-related risk factors of clinically significant prostate cancer (csPCa) undercategorized in patients with negative or equivocal MRI. Methods: This retrospective study included 581 patients with pathologically confirmed csPCa (Gleason score ≥ 3 + 4), including 108 undercategorized csPCa and 473 detected csPCa. All patients underwent multiparametric MRI (mpMRI). The undercategorized csPCa was defined as a MRI result with PI-RADS ≤ 3. The clinicopathological characteristics and imaging-related factors were compared between the undercategorized group(Group A) (PI-RADS 1–3) and detected group (Group B) (PI-RADS 4–5). Results: The age, total PSA levels, PSAD, free PSA, prostate imaging quality (PI-QUAL) scores, and Gleason scores were significantly lower in the Group A than Group B. The lesions were larger and involved in peripheral and transition zones in the Group B. A significant difference in the second reading opinion. Age (odds ratio [OR], 0.94), PSAD (OR, 0.09), and PI-QUAL scores (OR, 0.25) were significantly associated with the undercategorized csPCa. The rate of undercategorized csPCa with these three risk factors (age, PSAD, and PI-QUAL scores of < 71, < 0.355, and < 3, respectively) was 68.62%. The lack of zoomed-DWI resulted in lower PI-QUAL scores. Finally, the probability of undercategorized csPCa without zoomed DWI was 3.186 times higher than that with zoomed DWI when the PSAD ratio is lower than 0.355. Conclusions: Low image quality, younger age, and lower PSAD contribute to csPCa undercategorized by mpMRI. Moreover, the use of zoomed DWI decreased undercategorized csPCa by improving PI-QUAL scores of MRI images.